2014
DOI: 10.1111/ijlh.12204
|View full text |Cite
|
Sign up to set email alerts
|

Lower frequency of NPM1 and FLT3‐ITD mutations in a South African adult de novo AML cohort

Abstract: Introduction Acute myeloid leukemia (AML) is a heterogeneous clonal disorder of haemopoietic progenitor cells diagnosed in individuals of any age, but with a median age of 67 years at presentation in adults. Assessment of the mutation status of Nucleophosmin protein-1 (NPM1) and FMS-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD) are essential for the diagnosis, prognosis and treatment of AML. Methods A total of 160 de novo AML cases, both cytogenetically normal and abnormal, were analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In patients with FLT3 and NPM1 mutations, the associations of other genetic alterations have also been evaluated to understand any possible role in disease outcome. The prevalence of FLT3 and NPM1 mutations found in this population was in coherence with other studies (Asian and Western) despite geographic and ethnic differences (Tables 3, 4) [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 90%
“…In patients with FLT3 and NPM1 mutations, the associations of other genetic alterations have also been evaluated to understand any possible role in disease outcome. The prevalence of FLT3 and NPM1 mutations found in this population was in coherence with other studies (Asian and Western) despite geographic and ethnic differences (Tables 3, 4) [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that the gene mutations assessed for on the microarray might be population specific and are therefore not being detected. In 2014, Marshall et al reported a lower frequency of known NPM1 and FLT3 -ITD mutations in a South African AML cohort and suggested that race-specific mutations might contribute to AML pathogenesis and also to the lower frequency of detection of these mutations [ 14 ]. They further concluded that NPM1 mutation frequency increases with population age and that their cohort had a considerably younger median age at diagnosis, which might contribute to the lower frequency of NPM1 mutations observed in their study.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation is much less common 2-8% in pediatric AML and about 7.5% in younger median age AML cases [13,14,18,19]. Notably, Incidence of the NPM1 mutations is age-dependent as the mutation has not yet been identified in children younger than 3 years old, whereas the frequency is 10-19% in children older than 3 years and exceeds 30% in children older than 10 years [20,21].…”
Section: Npm1 Mutationsmentioning
confidence: 99%